2023
DOI: 10.1007/978-3-031-28719-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Shape and Pose for Object-Centric Deep Active Inference Models

Abstract: Active inference is a first principles approach for understanding the brain in particular, and sentient agents in general, with the single imperative of minimizing free energy. As such, it provides a computational account for modelling artificial intelligent agents, by defining the agent's generative model and inferring the model parameters, actions and hidden state beliefs. However, the exact specification of the generative model and the hidden state space structure is left to the experimenter, whose design c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the equivariant representation, the transformation to the input observation is preserved and cascaded into the intermediate space. Equivariant representations have been highly adopted in the context of machine learning [15,[24][25][26], and are considered crucial to achieving generalization features from the model at hand. The adoption of equivariant architectures is favoured in the research of 'disentangled' systems by the machine learning community where they have demonstrated their efficiency in generalization, imagination and abstraction reasoning.…”
Section: Symmetry In the Brainmentioning
confidence: 99%
“…In the equivariant representation, the transformation to the input observation is preserved and cascaded into the intermediate space. Equivariant representations have been highly adopted in the context of machine learning [15,[24][25][26], and are considered crucial to achieving generalization features from the model at hand. The adoption of equivariant architectures is favoured in the research of 'disentangled' systems by the machine learning community where they have demonstrated their efficiency in generalization, imagination and abstraction reasoning.…”
Section: Symmetry In the Brainmentioning
confidence: 99%